PROTOTIPE ALAT PEMIPIH MELINJO SEMI OTOMATIS - Adung Prawira Adinata; Syufrijal; Massus Subekti (Journal of Electrical Vocational Education and Technology, 2016)
ABSTRACT This research aims to design, create, and test the melinjo squashing machine that could control the electric motor semi-automaticly. The method used is the Research and Development. The design of a semi-automatic melinjo squashing machine is realized by combining multiple input and output components with a semi-automatic controller as a processing unit. Component inputs used are selectors that serves as a regulator for the machine to run manually or semi-automated and pushbutton function that manually would start the engine. Components such as controlling a semi-automatic process. Output components used function pilot lamp indicates the state of the engine and motor function squashier moving cylinder. From the research design tool semi automatic melinjo squashier outcome is successfully created and tested. The test results were obtained after the system was tested as a whole, so that it can be concluded that the design of semi-automatic tool of melinjo squashier work fine in accordance with the job description. Abstrak Penelitian ini bertujuan untuk membuat dan menguji mesin pemipih melinjo yang dapat menghidupkan motor listrik dengan semi otomatis. Metode penelitian yang digunakan adalah Research and Development. Prototipe mesin pemipih melinjo semi otomatis ini diwujudkan dengan menggabungkan beberapa komponen. Komponen input yang digunakan yaitu selektor yang berfungsi sebagai pengatur mesin agar dapat berjalan secara manual maupun semi otomatis dan pushbutton berfungsi menyalakan mesin secara manual. Komponen proses berupa pengendali semi otomatis. Komponen output yang digunakan pilot lamp berfungsi menandakan keadaan mesin, dan motor yang berfungsi menggerakan silinder pemipih. Dari hasil penelitian prototipe alat pemipih melinjo semi otomatis berhasil dibuat dan diuji. Hasil pengujian diperoleh setelah sistem diuji secara keseluruhan, sehingga dapat disimpulkan bahwa prototipe alat pemipih melinjo semi otomatis bekerja dengan baik sesuai dengan deskripsi kerja.